Local/global: amateur cinema and new forms of valorization in archival film festivals. Issue 3 (2nd September 2022) - Cavallotti, Diego; Simoni, Paolo
ABSTRACT: This paper will focus on the new landscapes of valorization and access to amateur/small gauge films within the archival film festival context. Archival small gauge film festivals present themselves as something completely different from those festivals dedicated to amateur and experimental cinema in the past, mainly because their goal is to valorize assets that have been deposited in specialized archives from the 1980s onwards. This film heritage is composed not only by the products of serious amateurs, but also by home movies and experimental films. We will start from the cases of Home Movie Day, a project developed in 2002 by archivists, curators and film historians in the US, Archivio Aperto in Italy, and Orphan Film Symposium, founded in 1999. Throughout the years they have become a blueprint for archival small gauge film festivals and a label to which different experiences refer: small archival film festivals; meeting activities where the broader field of 'non-theatrical film' is addressed; the Home Movie Marathon, a live streaming in which amateur films from all across the world are screened, etc. Furthermore, we will focus on examples from the European context, such as Archivio Aperto and its recent developments with the Memoryscapes digital platform.